The "Arab Spring": New Mechanisms of Change of Authoritarian Political Regimes - E. A. Antyukhova (Vestnik MGIMO-Universiteta, 2015)
The article explores the use of mechanisms in bringing down authoritarian political regimes in the Middle East and North Africa with the "Arab spring" in focus. The technique of "non-violent" methods of fight suggested by "godfather" of the "Arab spring" Gene Sharp is analyzed. It is noted that the distinctive features of his system were planned, determined and dynamic actions of protest forces. A special place in the article is devoted to the study of the role of non-governmental organizations in selecting and training protest leaders and activists and in creating a network of supporters of prodemocratic movements. The article examines the role of the Internet and cyber technologies used by the opposition during protest rallies. Non-violence as means of bringing down the existing power turned out to be an alternative to armed resistance. The key role of non-violent actions consisted in changing the point of view of anti-government forces, demonstrating that the public solidarity could make the regime overthrow possible. It is noted that the latest information means gave the process of political changes due activity and focus which was followed by the information actions designed to discredit the government in place and form the corresponding public opinion. Mediatization of politics promoted the creation of a dense information veil retouching a real picture. The overall system of methods used during the "the Arab spring" indicates that the mechanism of overthrowing authoritarian regimes and its technologies came from Western culture and were borrowed by Arab activists.